Job Burnout, Job Insecurity, and Quiet Quitting: The Mediating Role of Motivation in Startup Companies - Raisa Nur Agustin; Fansuri Munawar (Jurusan Akuntansi Politeknik Negeri Bandung, 2026)
This study addresses the growing phenomenon of quiet quitting among Millennial and Generation Z employees in startup companies, which has intensified following organizational efficiency measures and employment uncertainty. The research focuses on examining the effects of job burnout and job insecurity on quiet quitting, with motivation positioned as a mediating variable. The objective of this study is to explain the psychological mechanisms through which workplace stressors translate into disengagement behavior. A quantitative approach was employed using a survey method involving 157 Millennial and Generation Z employees working in startup companies in Bandung City that had experienced organizational efficiency measures. The data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results indicate that job burnout has a positive and significant effect on quiet quitting, while job insecurity does not directly influence quiet quitting. Motivation has a significant negative effect on quiet quitting and is negatively affected by both job burnout and job insecurity. Furthermore, motivation partially mediates the relationship between job burnout and quiet quitting and fully mediates the relationship between job insecurity and quiet quitting. These findings highlight the critical role of motivation in mitigating disengagement among young employees in uncertain work environments